PENGARUH KONSENTRASI KATALIS DAN WAKTU REAKSI PADA PEMBUATAN EPOKSI MINYAK GORENG BEKAS - Yenni Listiana, Hilde Rosa Tampubolon, Mersi Suriani Sinaga (Universitas Sumatera Utara, 2017)
Epoxy is produced from an epoxidation of vegetable oil or natural oil with au nsaturated bond. Epoxy can be applied as a stabilizer, plasticizers in polyvinyl chloride (PVC) and can be used as an antioxidant in natural rubber processing, as a surfactant, anti-corrosive additive agent in lubricants and pesticide raw materials. The purpose of this research was to evaluate epoxy production from waste cooking oil. In this research, waste cooking oil was reacted with hexane as solvent, sulfuric acid as catalyst, glacial acetic acid and hydrogen peroxide. The catalyst concentration was varied from 1.5%, 2.1%, 2.5%, 3.1% and 3.5% and the epoxidation time was varied from 60, 120, 180, 240 and 300 min. The results showed that highest epoxy yield was achieved at reaction time of 300 min and 1.5% catalyst. At that condition, the iod number was 0,96 g I2/100 g WCO, oxirane oxygen content was 1.872 and oxirane oxygen conversion was 62.259%.